Critique of the Centrals in Nietzsche’s Philosophy - Dahir, Riyam Mohammed; Al-Muhammadawi, Ali Abboud (Al-Adab Journal, 2021)
Nietzsche’s criticism, or his rejection of the previous philosophies, is a separating point between contemporary philosophy and the philosophies that preceded it, meaning that Nietzsche’s criticism of Greek philosophy, Christianity, contemporary as well as modern, and his criticism of the prevailing values ​​at that time (moral and religious) which he launched On it Nietzsche (slave ethics), critiqued and Nietzsche replaced traditional values ​​(Christian values) that express human submission to God, with creative values ​​in which they are superior to the status of the human self. To prove the human being, that is, Nietzsche rose up against religion, especially Christianity, and criticism of traditional metaphysics.